The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Pro-inflammatory response of human iPSC-derived intestinal epithelial monolayers towards microbial toxins LPS and nigericin - Germaine Aalderink; Hugo Brouwer; Jingxuan Wang; Aafke W. F. Janssen; Meike van der Zande; Coen Govers; Tamara Hoppenbrouwers; Hans Bouwmeester; Mathias Busch (Archives of Toxicology, 2026)
The intestinal epithelium forms a selective barrier between the intestinal lumen and the subepithelial layer. Intestinal epithelium plays a critical role in initiating inflammatory tissue responses in vivo, which remains challenging to emulate in vitro. Caco-2 cells are commonly used models of the intestinal epithelium, but lack crucial receptors and pathways associated with pro-inflammatory reactions. Human-induced pluripotent stem cell (iPSC)-based in vitro models are assumed to provide a system that better emulates in vivo responses. This study evaluated the inflammatory response of iPSC-derived intestinal epithelial cells (IEC) and Caco-2-derived intestinal epithelial cells to the microbial toxins lipopolysaccharide (LPS) and nigericin. Here, iPSCs were differentiated towards enterocyte, goblet- and Paneth-like cells without using three-dimensional culture techniques. The formed monolayer barriers were exposed to a combination of 0–100 µM nigericin and 100 ng/mL LPS on either the apical or basolateral side. The treatment-induced expression of cytokine genes and cytokine secretion were compared between the iPSC-derived cell model and differentiated Caco-2 cell layers. Nigericin exposure in combination with LPS significantly reduced transepithelial electrical resistance in the iPSC-derived model, and resulted in a tenfold increased secretion of the pro-inflammatory cytokines interleukin (IL)-6, IL-8, and tumor necrosis factor-alpha compared to the negative control. A similar increase was observed for the mRNA expression of these cytokines. No significant effect on TEER, cytokine secretion, or mRNA expression was observed in the Caco-2 model. Overall, this study shows that iPSC-IECs are a more sensitive model compared to Caco-2 to emulate inflammatory perturbations of the human intestinal epithelium.

OS02-04 From Toxicogenomics Data to Cumulative Assessment Groups: A Framework for Chemical Grouping - S. Canzler; J. Lehmann; J. Schor; W. Busch; G. Iacono; J. Hackermüller (Toxicology Letters, 2025)

P21-02 Comparing the effects of active substances and plant protection products in vitro using gene expression patterns in HepaRG cells and zebrafish embryos - A. Stagkos-Georgiadis; I. Suciu; W. Busch; D. Bloch (Toxicology Letters, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Allelochemicals determine competition and grazing control in Alexandrium catenella - Stefanie D. Moorthi; Michaela Busch; Ulrike Feudel; Urban Tillmann; Bernd Krock; Bob W. Kooi; Jana Brinkmann; Subhendu Chakraborty (Harmful Algae, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

High seroprevalence of feline morbilliviruses in free-roaming domestic cats in Chile - Johannes Busch; Irene Sacristán; Aitor Cevidanes; Javier Millán; Thomas W. Vahlenkamp; Constanza Napolitano; Michael Sieg (Archives of Virology, 2021)
Feline morbillivirus infections have gained increased attention due to repeated reports of their association with urinary tract disease in cats. In the present study, 112 serum samples from free-roaming domestic cats in Chile were tested for antibodies against feline morbillivirus genotypes 1 and 2 (FeMV-1 and FeMV-2) using an indirect immunofluorescence assay. In total, 63% of the animals showed antibodies against one or both FeMV genotypes. Antibodies directed exclusively against FeMV-2 were significantly more prevalent in male cats. The correlation of sex and FeMV-2 infection might give insight into potential routes of transmission. We provide, for the first time, serological data on FeMV in Chile.

Westward range expansion from middle latitudes explains the Mississippi River discontinuity in a forest herb of eastern North America - Carly J. Prior; Nathan C. Layman; Matthew H. Koski; Laura F. Galloway; Jeremiah W. Busch (Molecular Ecology, 2020)
It is often expected that temperate plants have expanded their geographical ranges northward from primarily southern refugia. Evidence for this hypothesis is mixed in eastern North American species, and there is increasing support for colonization from middle latitudes. We studied genome‐wide patterns of variation in RADseq loci to test hypotheses concerning range expansion in a North American forest herb ( Campanula americana ). First, spatial patterns of genetic differentiation were determined. Then phylogenetic relationships and divergence times were estimated. Spatial signatures of genetic drift were also studied to identify the directionality of recent range expansion and its geographical origins. Finally, spatially explicit scenarios for the spread of plants across the landscape were compared, using variation in the population mutation parameter and Tajima's D . We found strong longitudinal subdivision, with populations clustering into groups west and east of the Mississippi River. While the southeastern region was probably part of a diverse Pleistocene refugium, there is little evidence that range expansion involved founders from these southern locales. Instead, declines in genetic diversity and the loss of rare alleles support a westward colonization wave from a middle latitude refugium near the southern Appalachian Mountains, with subsequent expansion from a Pleistocene staging ground in the Mississippi River Valley (0.51–1.27 million years ago). These analyses implicate stepping stone colonization from middle latitudes as an important mechanism of species range expansion in eastern North America. This study further demonstrates the utility of population genetics as a tool to infer the routes travelled by organisms during geographical range expansion.

Diversity and distribution of the bmp gene cluster and its Polybrominated products in the genus Pseudoalteromonas - Julia Busch; Vinayak Agarwal; Michelle Schorn; Henrique Machado; Bradley S. Moore; Greg W. Rouse; Lone Gram; Paul R. Jensen (Environmental Microbiology, 2019)
Summary The production of pentabromopseudilin and related brominated compounds by Pseudoalteromonas spp. has recently been linked to the bmp biosynthetic gene cluster. This study explored the distribution and evolutionary history of this gene cluster in the genus Pseudoalteromonas . A phylogeny of the genus revealed numerous clades that do not contain type strains, suggesting considerable species level diversity has yet to be described. Comparative genomics revealed four distinct versions of the gene cluster distributed among 19 of the 101 Pseudoalteromonas genomes examined. These were largely localized to the least inclusive clades containing the Pseudoalteromonas luteoviolacea and Pseudoalteromonas phenolica type strains and show clear evidence of gene and gene cluster loss in certain lineages. Bmp gene phylogeny is largely congruent with the Pseudoalteromonas species phylogeny, suggesting vertical inheritance within the genus. However, the gene cluster is found in three different genomic environments suggesting either chromosomal rearrangement or multiple acquisition events. Bmp conservation within certain lineages suggests the encoded products are highly relevant to the ecology of these bacteria.

Climate‐driven reduction of genetic variation in plant phenology alters soil communities and nutrient pools - Ian M. Ware; Michael E. Van Nuland; Jennifer A. Schweitzer; Zamin Yang; Christopher W. Schadt; Lindsay C. Sidak‐Loftis; Nathan E. Stone; Joseph D. Busch; David M. Wagner; Joseph K. Bailey (Global Change Biology, 2019)
We examined the hypothesis that climate‐driven evolution of plant traits will influence associated soil microbiomes and ecosystem function across the landscape. Using a foundation tree species, Populus angustifolia , observational and common garden approaches, and a base population genetic collection that spans 17 river systems in the western United States, from AZ to MT, we show that (a) as mean annual temperature (MAT) increases, genetic and phenotypic variation for bud break phenology decline; (b) soil microbiomes, soil nitrogen (N), and soil carbon (C) vary in response to MAT and conditioning by trees; and (c) with losses of genetic variation due to warming, population‐level regulation of community and ecosystem functions strengthen. These results demonstrate a relationship between the potential evolutionary response of populations and subsequent shifts in ecosystem function along a large temperature gradient.

Elevated CO 2 impairs olfactory‐mediated neural and behavioral responses and gene expression in ocean‐phase coho salmon ( Oncorhynchus kisutch ) - Chase R. Williams; Andrew H. Dittman; Paul McElhany; D. Shallin Busch; Michael T. Maher; Theo K. Bammler; James W. MacDonald; Evan P. Gallagher (Global Change Biology, 2019)
Elevated concentrations of CO 2 in seawater can disrupt numerous sensory systems in marine fish. This is of particular concern for Pacific salmon because they rely on olfaction during all aspects of their life including during their homing migrations from the ocean back to their natal streams. We investigated the effects of elevated seawater CO 2 on coho salmon ( Oncorhynchus kisutch ) olfactory‐mediated behavior, neural signaling, and gene expression within the peripheral and central olfactory system. Ocean‐phase coho salmon were exposed to three levels of CO 2 , ranging from those currently found in ambient marine water to projected future levels. Juvenile coho salmon exposed to elevated CO 2 levels for 2 weeks no longer avoided a skin extract odor that elicited avoidance responses in coho salmon maintained in ambient CO 2 seawater. Exposure to these elevated CO 2 levels did not alter odor signaling in the olfactory epithelium, but did induce significant changes in signaling within the olfactory bulb. RNA‐Seq analysis of olfactory tissues revealed extensive disruption in expression of genes involved in neuronal signaling within the olfactory bulb of salmon exposed to elevated CO 2 , with lesser impacts on gene expression in the olfactory rosettes. The disruption in olfactory bulb gene pathways included genes associated with GABA signaling and maintenance of ion balance within bulbar neurons. Our results indicate that ocean‐phase coho salmon exposed to elevated CO 2 can experience significant behavioral impairments likely driven by alteration in higher‐order neural signal processing within the olfactory bulb. Our study demonstrates that anadromous fish such as salmon may share a sensitivity to rising CO 2 levels with obligate marine species suggesting a more wide‐scale ecological impact of ocean acidification.

A geographic cline in the ability to self‐fertilize is unrelated to the pollination environment - Matthew H. Koski; Dena L. Grossenbacher; Jeremiah W. Busch; Laura F. Galloway (Ecology, 2017)
The reproductive assurance ( RA ) hypothesis predicts that the ability to autonomously self‐fertilize should be favored in environments where a lack of mates or pollinators limits outcross reproduction. Because such limits to outcrossing are predicted to be most severe at range edges, elevated autonomy in peripheral populations is often attributed to RA . We test this hypothesis in 24 populations spanning the range of Campanula americana , including sampling at the range interior and three geographic range edges. We scored autonomous fruit set in a pollinator‐free environment and detected clinal variation—autonomy increased linearly from the southern to the northern edge, and from the eastern to the western edge. We then address whether the cline reflects the contemporary pollination environment. We measured population size, plant density, pollinator visitation, outcross pollen limitation and RA in natural populations over two years. Most populations were pollen limited, and those that experienced higher visitation rates by bumblebees had reduced pollen limitation. Reproductive assurance, however, was generally low across populations and was unrelated to pollen limitation or autonomy. Neither pollen limitation nor RA displayed geographic clines. Finally, autonomy was not associated with pollinator visitation rates or mate availability. Thus, the data do not support the RA hypothesis; clinal variation in autonomy is unrelated to the current pollination environment. Therefore, geographic patterns of autonomy are likely the result of historical processes rather than contemporary natural selection for RA .

Erratum to: Invasion of Bromus tectorum (L.) into California and the American Southwest: rapid, multi-directional and genetically diverse - Angela R. Pawlak; Richard N. Mack; Jeremiah W. Busch; Stephen J. Novak (Biological Invasions, 2015)

Invasion of Bromus tectorum (L.) into California and the American Southwest: rapid, multi-directional and genetically diverse - Angela R. Pawlak; Richard N. Mack; Jeremiah W. Busch; Stephen J. Novak (Biological Invasions, 2015)

Method Transfer, Partial Validation, and Cross Validation: Recommendations for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - R. J. Briggs; R. Nicholson; F. Vazvaei; J. Busch; M. Mabuchi; K. S. Mahesh; M. Brudny-Kloeppel; N. Weng; P. A. R. Galvinas; P. Duchene; Pei Hu; R. W. Abbott (The AAPS Journal, 2014)

Demographic and population‐genetic tests provide mixed support for the abundant centre hypothesis in the endemic plant Leavenworthia stylosa - Andrea L. Dixon; Christopher R. Herlihy; Jeremiah W. Busch (Molecular Ecology, 2013)
The abundant centre hypothesis ( ACH ) assumes that population abundance, population size, density and per‐capita reproductive output should peak at the centre of a species' geographic range and decline towards the periphery. Increased isolation among and decreased reproductive output within edge populations should reduce within‐population genetic diversity and increase genetic differentiation among edge relative to central populations. The ACH also predicts asymmetrical gene flow, with net movement of migrants from the centre to edges. We evaluated these ecological assumptions and population‐genetic predictions in the endemic flowering plant Leavenworthia stylosa . Although populations were more spatially isolated near range edges, the geographic centre was surrounded by and not coincident with areas of peak population abundance, and plant density increased towards range edges. Per‐capita seed number was not associated with distance to the range centre, but seed number/m 2 increased near range edges. In support of ACH predictions, allelic diversity at 12 microsatellite loci declined with distance from the range centre, and pairwise F ST values were higher between edge populations than between central populations. Coalescent analyses confirmed that gene flow was most infrequent between edge populations, but there was not an asymmetric pattern of gene flow predicted by the ACH . This study shows that among‐population demographic variability largely did not support the ACH , while patterns of genetic diversity, differentiation and gene flow were generally consistent with its predictions. Such mixed support has frequently been observed in tests of the ACH and raises concerns regarding the generality of this hypothesis for species range limits.

Deep-water life cycle of Anisakis paggiae (Nematoda: Anisakidae) in the Irminger Sea indicates kogiid whale distribution in north Atlantic waters - Sven Klimpel; Thomas Kuhn; Markus W. Busch; Horst Karl; Harry W. Palm (Polar Biology, 2011)

Insights Gained From 50 Years of Studying the Evolution of Self-Compatibility in Leavenworthia (Brassicaceae) - Jeremiah W. Busch; Lillis Urban (Evolutionary Biology, 2011)

Dynamics of well-folded and natively disordered proteins in solution: a time-of-flight neutron scattering study - A. M. Gaspar; M.-S. Appavou; S. Busch; T. Unruh; W. Doster (European Biophysics Journal, 2008)

Nachweis von Clostridium botulinum Typ A, B, E und F mittels real-time-PCR - U. Messelhäusser; R. Zucker; H. Ziegler; D. Elmer-Englhard; W. Kleih; C. Höller; U. Busch (Journal of Consumer Protection and Food Safety, 2007)

Real-time-PCR-System zum Nachweis von Bacillus cereus (emetischer Typ) in Lebensmitteln - U. Messelhäusser; M. Fricker; M. Ehling-Schulz; H. Ziegler; D. Elmer-Englhard; W. Kleih; U. Busch (Journal of Consumer Protection and Food Safety, 2007)

The Use of Poly(Sodium N-Undecanoyl-l-Leucylvalinate), Poly(Sodium N-Undecanoyl-l-Leucinate) and Poly(Sodium N-Undecanoyl-l-Valinate) Surfactants as Chiral Selectors for Determination of Enantiomeric Composition of Samples by Multivariate Regression Modeling of Fluorescence Spectral Data - Sayo O. Fakayode; Alicia A. Williams; Marianna A. Busch; Kenneth W. Busch; Isiah M. Warner (Journal of Fluorescence, 2006)

Epidemiology of rubella infections in Austria: important lessons to be learned - B. Falkensammer; G. Walder; D. Busch; A. Gieauf; M. Dierich; R. Wrzner (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

A Statistical Approach to Estimate Spatial Distributions of Wet Deposition in Germany - W. Vautz; A. U. Busch; W. Urfer; D. Klockow (Water, Air, & Soil Pollution, 2003)

Genetic Variation and Relationships of Constitutive and Herbivore-Induced Glucosinolates, Trypsin Inhibitors, and Herbivore Resistance in Brassica rapa - Donald F. Cipollini; Jeremiah W. Busch; Kirk A. Stowe; Ellen L. Simms; Joy Bergelson (Journal of Chemical Ecology, 2003)

Use of the firefly luciferase gene in a barley ( Hordeum vulgare ) transformation system - W. Harwood; S. Ross; S. Bulley; S. Travella; B. Busch; J. Harden; J. Snape (Plant Cell Reports, 2002)

The K ATP channel blocker HMR 1883 does not abolish the benefit of ischemic preconditioning on myocardial infarct mass in anesthetized rabbits - O. Jung; H.C. Englert; W. Jung; H. Gögelein; B.A. Schölkens; A.E. Busch; W. Linz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Agronomic performance of lines derived from anther culture, maize pollination and single-seed descent in a spring wheat cross - H. Ma; R. H. Busch; O. Riera-Lizarazu; H. W. Rines; R. Dill-Macky (Theoretical and Applied Genetics, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Structural rearrangement in chromosome 2M of Aegilops comosa has prevented the utilization of the Compair and related wheat-Ae. comosa translocations in wheat improvement - S. Nasuda; B. Friebe; W. Busch; R. G. Kynast; B. S. Gill (Theoretical and Applied Genetics, 1998)